Immune Cell-Based versus Albumin-Based Ratios as Outcome Predictors in Critically Ill COVID-19 Patients - Zeba S; Surbatovic M; Udovicic I; Stanojevic I; Vojvodic D; Rondovic G; Mladenovic K; Abazovic T; Hasanovic A; Ilic AN; Abazovic D; Khan W; et al. (Journal of Inflammation Research)
Snjezana Zeba,1 Maja Surbatovic,2 Ivo Udovicic,1 Ivan Stanojevic,3 Danilo Vojvodic,3 Goran Rondovic,1 Katarina Mladenovic,1 Tanja Abazovic,2 Almina Hasanovic,4 Aleksandra N Ilic,5 Dzihan Abazovic,6 Wasim Khan,7 Dragan Djordjevic1 1Clinic of Anesthesiology and Intensive Therapy, Military Medical Academy, Faculty of Medicine of the Military Medical Academy, University of Defense, Belgrade, Serbia; 2Clinic of Anesthesiology and Intensive Therapy, Military Medical Academy, Belgrade, Serbia; 3Institute for Medical Research, Military Medical Academy, Faculty of Medicine of the Military Medical Academy, University of Defense, Belgrade, Serbia; 4Nephrology Clinic, Military Medical Academy, Belgrade, Serbia; 5Faculty of Medicine, University of Pristina, Kosovska Mitrovica, Serbia; 6Atlas Hospital, Belgrade, Serbia, Aba Medica Healthcare Centre, Ulcinj, Montenegro; 7Division of Trauma & Orthopaedic Surgery, University of Cambridge, Addenbrooke’s Hospital, Cambridge, CB2 2QQ, UKCorrespondence: Maja Surbatovic, Clinic of Anesthesiology and Intensive Therapy, Military Medical Academy, 17 Crnotravska Street, Belgrade, 11000, Serbia, Tel +381 11 2665 125, Email maja.surbatovic@gmail.comPurpose: The aim of the retrospective, single-center study was to assess the prognostic value of immune cell-based and albumin-based ratios regarding lethal outcome in critically ill COVID-19 patients.Patients and Methods: We analyzed 612 adult critically ill COVID-19 patients admitted to the intensive care unit (ICU) between April 2020 and November 2022. Blood measurement on admission to the ICU encompassed complete blood count (CBC), IL-6, C-reactive protein (CRP), albumin, lactate, lactate dehydrogenase (LDH), serum bicarbonate, arterial base deficit/excess (BD/E), and D-dimer. All the measured and calculated parameters were compared between survivors and nonsurvivors, with the outcome measure being hospital mortality.Results: Immune cell-based ratios [NLR - Neutrophil-to-Lymphocyte Ratio, MLR - Monocyte-to-Lymphocyte Ratio, PLR - Platelet-to-Lymphocyte Ratio, MPV - Mean Platelet Volume, MPV/PC - Mean Platelet Volume-to-Platelet Count Ratio, Derived (d-)NLR ratio - neutrophil count divided by the result of white blood cell (WBC) count – neutrophil count), N/LP - Neutrophil count x 100/Lymphocyte count x Platelet count, CLR – C-reactive protein (CRP)-to-Lymphocyte Ratio, CPR - CRP-to-Platelet Ratio, LLR - Lactate dehydrogenase (LDH)-to-Lymphocyte Ratio, Systemic Immune Inflammation Index (SII) - platelet x neutrophil/lymphocyte count, Systemic Inflammation Response Index (SIRI) - neutrophil x monocyte/lymphocyte count] were investigated. White blood cell and neutrophil counts were significantly higher, while lymphocyte and platelet counts were significantly lower in nonsurvivors. MPV, MPV/PC, NLR, d-NLR, MLR, N/LP, CRP, LDH, CPR, CLR, LLR, SII, and SIRI values were significantly higher in nonsurvivors. Monocyte count and PLR values did not differ significantly between groups. Albumin-based ratios included CRP-to-Albumin Ratio (CAR), Lactate-to-Albumin Ratio (LAR) and LDH-to-Albumin Ratio (LDH/ALB). All values were significantly higher in nonsurvivors.Conclusion: The only independent predictor of lethal outcomes at ICU admission is the albumin-based LDH/ALB ratio. Most of the other parameters were moderate, although highly significant predictors of mortality in critically ill COVID-19 patients.Keywords: LDH/albumin ratio, critically ill, COVID-19, mortality